Comparative Evaluation of Pre-Induction Changes in Bishop’s Score with Insertion of Intra-Cervical Foley Catheter and Vaginal Misoprostol - Mandal, Anju (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aim: The aim of this study was to compare changes in pre-induction Bishop’s Score with insertion of intra-cervical Foley catheter and vaginal Misoprostol administration for cervical ripening. Methods: It is a comparative study done among 50 patients at term that had Bishop’s score <5 in College of Medical Science in Bharatpur. Intra-cervical Foley catheter was used in half of the women and intra-vaginal insertion of 50 microgram Misoprostol tablet was used in the rest. After 24 hours of post ripening, Bishop’s score was noted and labour was induced with inj. oxytocin if required. Results: Both groups showed significant changes in the mean Bishop’s score after ripening agents, 7.64 and 7.25 for Foley catheter group and Misoprostol group respectively. Eighty four percent patients from Foley catheter group and 72% patient from Misoprostol had normal delivery. Conclusion: Post ripening mean Bishop’s score was significantly better in Foley catheter group as compared to Misoprostol group.The induction to labour interval, induction to delivery interval and labour to delivery interval were less in Foley’s catheter group than Misoprostol group.